Alternative Methotrexate Oral Formulation: Enhanced Aqueous Solubility, Bioavailability, Photostability, and Permeability - Bhupendra Raj Giri; Hyun Seok Yang; Im-Sook Song; Han-Gon Choi; Jung Hyun Cho; Dong Wuk Kim (MDPI AG, 2022)
The poor aqueous solubility and/or permeability and thereby limited bioavailability largely restricts the pharmaco-therapeutic implications of potent anticancer drugs such as methotrexate (MTX). Furthermore, MTX's inherently unstable nature makes it difficult to develop a viable oral formulation. In this study we developed the spray-dried amorphous inclusion complexes of MTX with native β-cyclodextrin (β-CD) and its derivatives, namely HP-β-CD, M-β-CD, and DM-β-CD to enhance the aqueous solubility, photostability, permeability, and oral bioavailability of MTX in rats. Our findings show that the 1:1 stoichiometry ratio of MTX and CDs improves the aqueous solubility, stability, and pharmacokinetic profiles of the drug, the better results being obtained particularly with DM-β-CD as a host, which has a higher complexation ability with the drug compared to other β-CDs. Specifically, the pharmacokinetic analysis demonstrated 2.20- and 3.29-fold increments in AUC and Cmax, respectively, in comparison to free MTX. Even though the absorptive permeability of MTX and MTX/DM-β-CD inclusion complexes was similar, the efflux of the absorbed MTX from ICs was significantly lower compared to the free MTX (4.6- vs. 8.0-fold). Furthermore, the physicochemical characterization employing SEM, DSC, and PXRD confirmed the transformation of crystalline MTX to its amorphous state. In solution, 1H NMR studies revealed that MTX embedded into the DM-β-CD cavity resulting in both H-3 and H-5 chemical shifts implied the presence of intermolecular interaction between the drug and CD moiety. It was, therefore, evident that an MTX IC could be a successful oral formulation technique, preventing MTX degradation and enhancing its pharmacologically relevant properties.